Clinical Experience With a New Type of Rhino-Larynx Electronic Endoscope PENTAX VNL-1530. Issue 1 (1994) - Kawaida, Masahiro; Fukuda, Hiroyuki; Kohno, Naoyuki
Abstract : We observed recordings of pictures obtained from patients with diseases of the larynx by using a new type of rhino-larynx electronic endoscope, PENTAXVNL-1530 connected to a video processor, PENTAX EPM-3300 (Asahi Optical Co., Ltd.). The electronic endoscope differs from the fiberoptic endoscope in that it contains a small light-sensitive charge coupled device (CCD) chip that is attached to the tip of the endoscope. This electronic endoscope has the smallest CCD camera of 5.1 mm in diameter, in the tip portion, and can be passed through the nasal passage into the laryngeal cavity. The dynamic image provided by this system is superior to that obtained by a flexible laryngofiberscope in resolution of the detail. The system with this electronic endoscope was introduced and some clinical cases were presented.